Trends and age-period-cohort analysis of migraine incidence in China from 1990 to 2021 - Yuting Huang; Dongxue Liu; Hongxiao Zhang; Xufang Xu; Shuangshuang Yuan; Shaoyang Cui; Zhihua Peng; Run Zhang (PLoS ONE, 2026)
Objective The rapid economic development and demographic changes in Chinese society in the past 30 years may affect the prevalence of migraine. However, there are limited studies on the long-term trends and influencing factors of migraine burden in China. Using data from global burden of disease database (GBD2021), this study explores the changes in the migraine burden in China over a 30-year period and analyzes the main drivers. Methods Joinpoint regression analysis was used to evaluate the temporal trend of migraine prevalence, incidence, and years lived with disability (YLDs), and the age-period-cohort (APC) model was used to evaluate the effects of age, time and birth cohort. Decomposition analysis were used to calculate the contribution of population growth, ageing, and epidemiological changes to the burden of disease. Results In the past 30 years, the age-standardized prevalence rate (ASPR) and YLDs rate of migraine in China have increased significantly, and the disease burden of women is higher than that of men, especially in people aged 30–54 years. The main driver of the rising burden of disease is population growth. APC analysis showed that the younger generation had a higher burden of disease, which may be related to modern lifestyles and stressors. Conclusion The burden of migraine continues to increase in China, which is mainly affected by population growth and epidemiological changes. In the future, attention should be paid to high-risk groups, and lifestyle interventions and disease management should be strengthened to reduce the socio-economic burden.